Smernice za odmerjanje finančnih popravkov sredstev EU - Rejc, Žiga (Javna uprava, 2021)
The author analyses legal nature of the Guidelines on Financial Corrections by the European Commission, as well as legal boundaries of their application. In the second part of the article, the author also focuses on jurisprudence of Slovenian courts regarding the legal basis for using the Commission’s Guidelines in the procedures, in which the State claims payment of financial corrections from final recipients of the (EU) funding. The author argues that these Guidelines are not regulation by themselves. Therefore, the Guidelines could only be directly legally relevant for these legal relations, if their application was either required by national law or contractually agreed with the beneficiary.
Keywords: Commission; EU funding; Evropska komisija; Evropska unija; financial corrections; finančni instrumenti; guidelines; javne finance; nepovratna sredstva; sredstva EU